Reconfigurable Computing: Architectures, Tools and Applications : 9th International Symposium, ARC 2013, Los Angeles, CA, USA, March 25-27, 2013. Proceedings - Figueiredo Coutinho, Jose Gabriel; Diniz, Pedro C.; Brisk, Philip (Lecture notes in computer science, 2013)
This book constitutes the thoroughly refereed conference proceedings of the 9th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2013, held in Los Angeles, CA, USA, in March 2013. The 28 revised papers presented, consisting of 20 full papers and 11 poster papers were carefully selected from 41 submissions. The topics covered are applications, arithmetic, design optimization for FPGAs, architectures, place and routing.